2011
DOI: 10.1111/j.1471-4159.2011.07414.x
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine metabolism predicts cognitive function in patients following cardiac bypass and thoracic surgery

Abstract: Cardiac surgery involving extra-corporeal circulation can lead to cognitive dysfunction. As such surgery is associated with signs of inflammation and pro-inflammatory mediators activate tryptophan oxidation to neuroactive kynurenines which modulate NMDA receptor function and oxidative stress, we have measured blood concentrations of kynurenines and inflammatory markers in 28 patients undergoing coronary arterial graft surgery and, for comparison, 28 patients undergoing non-bypass thoracic surgery. A battery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 94 publications
(91 reference statements)
4
33
1
1
Order By: Relevance
“…Spatial discrimination, passive avoidance and object exploration/recognition, is enhanced in KAT II knock-out mice with reduced brain KYNA levels37 and impaired memory, passive avoidance and elevated brain KYNA, is associated with reduced cognitive flexibility in offspring of dam rats fed with KYNA-containing chow under the gestational period 38,39. In bypass patients, KYNA has been shown to function as a predictor of poor cognitive performance related to frontal executive functions and memory 40. The lack of a correlation between CSF KYNA and MMSE in the present study could thus be related to the design of the cognitive test.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial discrimination, passive avoidance and object exploration/recognition, is enhanced in KAT II knock-out mice with reduced brain KYNA levels37 and impaired memory, passive avoidance and elevated brain KYNA, is associated with reduced cognitive flexibility in offspring of dam rats fed with KYNA-containing chow under the gestational period 38,39. In bypass patients, KYNA has been shown to function as a predictor of poor cognitive performance related to frontal executive functions and memory 40. The lack of a correlation between CSF KYNA and MMSE in the present study could thus be related to the design of the cognitive test.…”
Section: Discussionmentioning
confidence: 99%
“…Forrest et al (2011) reported no difference in blood KYNA in patients undergoing CABG during and up to 2 days after cardiac surgery and an increase in plasma KYNA on the sixth postoperative day. They also noted no changes in plasma KYNA in patients undergoing thoracic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…KYNA production is also elevated during a bacterial or viral inflammation, an autoimmune disease and after a severe trauma (Forrest et al 2006; Hartai et al 2007; Scott et al 2009; Zeden et al 2010). Increases in plasma tryptophan metabolites have also been observed in patients undergoing elective abdominal or cardiac surgery (Forrest et al 2011; Marfella et al 1999). Perioperative increases in plasma cytokine concentrations following surgery-related inflammatory response may affect plasma KYNA concentration.…”
Section: Introductionmentioning
confidence: 99%
“…By consuming tryptophan, IDO activation can therefore, in turn, reduce the synthesis of serotonin. Association of neuropsychiatric symptoms with increased kynurenine levels or altered kynurenine/tryptophan ratio has been demonstrated in several conditions associated with inflammation, including IFN-α-treated patients, aging, or Alzheimer's disease (Capuron et al, 2011c;Gulaj et al, 2010;Forrest et al, 2011;Gold et al, 2011;Raison et al, 2010). Microglial activation of the kynurenine pathway can also ultimately lead to the production of neuroactive glutamatergic compounds, including 3-hydroxykynurenine and quinolinic acid, which have a key role in neuronal death by stimulating NMDA receptors and promoting oxidative stress (Campbell et al, 2014;Dantzer and Walker, 2014;Stone et al, 2012).…”
Section: Neuropsychiatric Effects Of Inflammation: Evidence and Mechamentioning
confidence: 99%